2014
DOI: 10.1159/000356567
|View full text |Cite
|
Sign up to set email alerts
|

Interest and Informational Preferences Regarding Genomic Testing for Modest Increases in Colorectal Cancer Risk

Abstract: Background/Aims: This study explored the interest in genomic testing for modest changes in colorectal cancer risk and preferences for receiving genomic risk communications among individuals with intermediate disease risk due to a family history of colorectal cancer. Methods: Surveys were conducted on 272 men and women at intermediate risk for colorectal cancer enrolled in a randomized trial comparing a remote personalized risk communication intervention (TeleCARE) aimed at promoting colonoscopy to a generic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
(56 reference statements)
2
14
0
Order By: Relevance
“…It is possible that many of the study participants were primed to expect high quality information from various sources. Our results agree with similar studies showing that a majority of participants prefer to receive genetic information through a physician or genetic counselor and also prefer print materials (Anderson et al, 2014; McGuire et al, 2009). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is possible that many of the study participants were primed to expect high quality information from various sources. Our results agree with similar studies showing that a majority of participants prefer to receive genetic information through a physician or genetic counselor and also prefer print materials (Anderson et al, 2014; McGuire et al, 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Unmarried participants reported a greater interest in genetic testing, but this factor was not significant in multivariable analysis. The relationship between marital status and interest in cancer genetic testing is inconsistent across studies and could be a reflection of the different populations studied (Anderson et al, 2014; Graves et al, 2011; Weinrich et al, 2002). However, our current finding (unmarried women were more interested in testing) is consistent with findings from our previous study regarding interest in multiplex testing for colorectal cancer risk (Anderson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite commercial availability, there is limited data reporting on the implementation of polygenic breast cancer risk information and uptake of the test. Prior studies have been limited to hypothetical scenarios or based on single SNP testing . These studies have reported a high interest in SNP testing, with interest ranging from 74% to 80% .…”
Section: Introductionmentioning
confidence: 99%
“…In the population, health awareness is a growing issue [1,63] . In connection with the ongoing reports of new genetic findings, curiosity and interest about health risks also increase [64,65] . Vayena [66] investigated the reasons for undergoing genetic testing.…”
Section: Discussionmentioning
confidence: 99%